APPLICATION OF MODIFIED KOZENY-CARMAN METHOD TO CHARACTERIZE ROCK TYPE AND ESTIMATE PERMEABILITY IN UNCORED ZONE - Erichatama, Nadya
The Kozeny-Carman equation has been used extensively as a rock typing technique and determining permeability values. Modifications to this method have been made by several authors. Marhaendrajana and Marsusi (2012) modified this equation by substituting surface area of grain with porosity, irreducible water saturation, and water film thickness. In this thesis, the normalization of water saturation data is proposed to be done first before rock typing using the Marhaendrajana and Marsusi methods. In this study, the application of several rock typing and permeability prediction methods based on Kozeny-Carman was carried out in sandstone and carbonate fields. The proposed method gives fairly good results in the classification of rock types and determining the value of permeability on sandstone reservoir.